Analisis Variabel Penyebab Balita Gizi Buruk di Provinsi Jawa Timur Tahun 2015 - Lisa Agustin (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
The East Java Province has successfully overcome the incidences of malnutrition. In 2015, the number of malnutrition cases was 6,745 (1.8 percent), which was lower than the targets of MDGs (15.0 percent) and the Strategic Plans of the Ministry of Health of the Republic of Indonesia (15.0 percent). However, according to National data (Dinkes, 2015), East Java was the second largest province with the highest cases of child malnutrition after the East Nusa Tenggara Province. The study aims to explain the direct and indirect causes of malnutrition among children under five years of age in the East Java Province in 2015. Using secondary data from the 2015 National Economic Social Survey in the East Java Province, the subjects of this research consisted of 38 districts and municipalities in the East Java Province. The results showed that the p values for each variable are: the length of breastfeeding in infants aged 0–23 months (X1) was 0.007, the percentage of completed immunization children under five years (X2) was 0.011, the percentage of the population consumption below 1400 kcal (X3) was 0.960, the proportion of households with adequate sanitation (X4) was 0.198, and the ratio of Enrolment Rates in Senior High Schools between female and male (X5) was 0.439. The conclusion of this study is that the independent variables were the time length of mothers in breastfeeding their infants aged 0–23 months and the percentage of children under five years of age who were fully immunized which had a negative correlation with malnutrition experinced by children under five years of age in the East Java Province in 2015.